Answer: i think the answer is d or c im not to sure
Step-by-step explanation:
Measure of Hypotaneous = 5√5
And it's already given that b = 2a
By using pythagoras theorem:
a²+ b² = (5√5)²
Let's substitute for b as 2a in above equation we'll get:
a² + (2a)² = (5√5)²
a² + 4a² = 125
5a² = 125
a² = 25
a = √25 = 5
Therefore,
a= 5
and
b = 2a = 2(5) = 10.
Hello, MissMisty here to help you.
<span>• </span>The answer •
Y = -3/4 + 3
Thanks! I hope it helped you, I'm glad I could help if it did. Have a good morning.
Answer:
![\boxed{\sf x=-2}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Csf%20x%3D-2%7D)
![\boxed{\sf y=-4}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Csf%20y%3D-4%7D)
Step-by-step explanation:
<u>First, Let's solve for x in -2x+2y=-4:</u>
![\sf -2x+2y=-4](https://tex.z-dn.net/?f=%5Csf%20-2x%2B2y%3D-4)
<u>Subtract 2y from both sides:</u>
![\sf -2x+2y-2y=-4-2y](https://tex.z-dn.net/?f=%5Csf%20-2x%2B2y-2y%3D-4-2y)
![\sf -2x=-4-2y](https://tex.z-dn.net/?f=%5Csf%20-2x%3D-4-2y)
<u>Divide both sides by -2:</u>
![\sf \cfrac{-2x}{-2}=-\cfrac{4}{-2}-\cfrac{2y}{-2}](https://tex.z-dn.net/?f=%5Csf%20%5Ccfrac%7B-2x%7D%7B-2%7D%3D-%5Ccfrac%7B4%7D%7B-2%7D-%5Ccfrac%7B2y%7D%7B-2%7D)
![\bold{ x=y+2}](https://tex.z-dn.net/?f=%5Cbold%7B%20x%3Dy%2B2%7D)
<u>Now, we'll substitute x=y+2 to 3x+3y=-18:</u>
![\sf 3x+3y=-18](https://tex.z-dn.net/?f=%5Csf%203x%2B3y%3D-18)
→ let x=2+y
![\sf 3\bold{(2+y)}+3y=-18](https://tex.z-dn.net/?f=%5Csf%203%5Cbold%7B%282%2By%29%7D%2B3y%3D-18)
<u>Simplify:</u>
![\sf 6+6y=-18](https://tex.z-dn.net/?f=%5Csf%206%2B6y%3D-18)
<u>Now, let's solve for y in 6+6y=-18</u>
![\sf 6+6y=-18](https://tex.z-dn.net/?f=%5Csf%206%2B6y%3D-18)
<u>Subtract 6 from both sides:</u>
![\sf 6+6y-6=-18-6](https://tex.z-dn.net/?f=%5Csf%206%2B6y-6%3D-18-6)
![\sf 6y=-24](https://tex.z-dn.net/?f=%5Csf%206y%3D-24)
<u>Divide both sides by 6:</u>
![\sf \cfrac{6y}{6}=\cfrac{-24}{6}](https://tex.z-dn.net/?f=%5Csf%20%5Ccfrac%7B6y%7D%7B6%7D%3D%5Ccfrac%7B-24%7D%7B6%7D)
![\bold{ y=-4}](https://tex.z-dn.net/?f=%5Cbold%7B%20y%3D-4%7D)
<u>Now, substitute y=-4 into x=2+y:</u>
![\sf x=2+y](https://tex.z-dn.net/?f=%5Csf%20x%3D2%2By)
→ let y = -4
![\sf x=2+\bold{-4}](https://tex.z-dn.net/?f=%5Csf%20x%3D2%2B%5Cbold%7B-4%7D)
![\bold{x=-2}](https://tex.z-dn.net/?f=%5Cbold%7Bx%3D-2%7D)
Therefore, x=-2 and y=-4.
<u>_____________________________________</u>